A comparative study of postoperative airway management between traditional nasal packing and modified nasal airway after nasal surgeries - Muhammad Saleem; Baber Rafiq Khan; Sarwat Bibi; Humaira Ahmad; Muhammad Hamza Rana (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: One of the most common challenging complications after nasal surgeries is maintaining airways. The study aimed to use an alternative technique instead of nasal packing in the immediate postoperative period undergoing different nasal surgery under general anesthesia regarding airway management. METHODOLOGY: An interventional study was conducted at Aziz Fatimah Trust Hospital, Faisalabad, from March 20, 2018, to January 31, 2019. A total of 100 participants were enrolled in the study divided into two groups (A & B), 50 each. Group A patients were treated postoperatively with a modified nasal airway devised with a Nelton catheter and Group B patients with traditional nasal packing. The participants were assessed on different parameters which were statistically compared and analyzed. RESULTS: Group Descriptive statistics revealed that the Mean±SD of the age of group A and group B patients was 24.28±9.72 and 26.68±11.09 respectively, which had no significant difference between them p-value (0.008). The postoperative parameters such as patient’s comfort and sleep, surgeon satisfaction, ease of suction through Nelton catheter, and oxygen saturation were evaluated as significant variables in the evaluation of the study. p-value ≤0.05 and ≤0.005 were considered as significant and highly significant respectively. CONCLUSION: This modified nasal airway has proven to be easily replicable and reliable, and a cost-effective measure elucidated as a potential and exclusive outcome of the present study.